The labour market and financial consequences of relationship breakdown and re-partnering of mothers with young children - Baxter, Jennifer; Gray, M (My University, 2008)
While the majority of children live in stable couple families, some experience changes in the relationship status of their parents, even while they are young. Some experience their parents' relationship breakdown and some experience the re-partnering of one or both parents. There are many ways this might impact on children, but an important aspect is how such transitions are associated with parents' changes in financial wellbeing. This paper focuses on this association between relationship breakdown or repartnering and changes in financial wellbeing. We also consider changes in parent's participation in the paid labour market as part of this. The analyses make use of two waves of data from the Longitudinal Study of Australian Children (LSAC), the first wave having been collected in 2004, and the second in 2006. Changes in relationship status of parents, in labour market participation and in financial wellbeing are examined for this two-year time period. As LSAC is a study of young children, the analysis provides insights about this important time in children's lives.
Keywords: Relationships; Relationships -- Dissolution; Families and relationships; Relationships; Dissolution; Families and relationships